Sample preparation optimization for the simultaneous determination of mycotoxins in cereals - Rahmani, Anoshep; Jinap, Selamat; Soleimany, F.; Khatib, Alfi; Tan, Chin Ping (Springer-Verlag, 2011)
The efficiency of three extraction solvents and three clean-up procedures was compared for simultaneous extraction and purification of aflatoxins (AFB1, AFB2, AFG1 and AFG2), ochratoxin A (OTA), and zearalenone (ZEA) from spiked cereal samples. The best recovery rates for all mycotoxins were achieved using methanol: water (80:20) as the extraction solvent and AOZ multi-functional immunoaffinity column (IAC), as clean up method with recovery values of 61–89%, while that of Oasis HLB and MycoSep 226 were 37–67% and 44–78%, respectively. Then, five variables in the IAC clean-up conditions, including primary conditioning with phosphate buffer saline (PBS) (0–10 mL) (X1), extract load up volume (10–20 mL) (X2), washing volume with PBS (10–20 mL) (X3), and eluting solution volumes with methanol (1–3 mL) (X4) and acetic acid (0–1.5 mL) (X5), were optimized for the specific purification and enrichment of the mycotoxins. Results showed that primary conditioning and PBS washing did not have a significant effect on the recovery responses of mycotoxins. Optimized conditions were selected as 0, 15, 10, 1.3, and 1.5 mL for X1–X5, respectively. The recovery rates of AFB1, AFB2, AFG1, AFG2, OTA and ZEA were within 93–104% in spiked rice, under optimal conditions. LOD and LOQ were 0.0125 and 0.05 ng/g for AFB1 and AFG1, 0.0037 and 0.015 ng/g for AFB2 and AFG2, 0.05 and 0.2 ng/g for OTA, and 0.5 and 2 ng/g for ZEA, respectively. Extraction of spiked cereal samples with methanol: water (80:20) and clean up using AOZ IAC column in optimal condition provided recovery range of 77–104% for all targeted mycotoxins.